Phytochemical Composition, Antioxidant and Antimicrobial Potentials of some Indigenous Plants in Umudike, Abia State, Nigeria - J. C. Nnaji; J. F. Amaku; C. M. Ngwu; H. O. Chukwuemeka-Okorie; K. G. Akpomie; B. I. Ugwu; M. Z. Siyaka; S. A. Odoemelam (Journal of Applied Sciences and Environmental Management, 2022)
Twenty four ethanol leaf and stem bark extracts of 17 indigenous plants were examined for their phytochemical composition, antimicrobial and antioxidant properties. Phytochemical compositions were analysed with GC-MS while antimicrobial activities on Staphylococcus aureus and Pseudomonas aeruginosa were investigated by the agar well diffusion method. The antioxidant activities were determined with Ferric reducing antioxidant power (FRAP), total phenolic content (TPC) and 2, 2,-dihenyl-1-picryhydazyl (DPPH) radical scavenging assays. The antibacterial activity was more towards the gram positive S. aureus than the gram negative P. aeruginosa for all the plant extracts.  A wide range of phenolic concentrations among the aqueous plant extracts which varied from 28.04 to 500.26mg GAE per gram were observed.  Inhibition percentages of DPPH ranged from 19.13 to 95.77% showing effectiveness in radical scavenging. GC-MS characterization of the plant extracts showed a total of 18 components including alkaloids, flavonoids, phenols, saponins, terpenoids, steroids and glycosides. Irvingia gabonensis leaf (IGL) extract and Tamarind stem bark (TSB) exhibited excellent ferric reducing abilities of 2.11 and 1.56 respectively while Voucanga Africana leaf (VCA) extract indicated the lowest ferric reducing power of 0.50. Extracts of IGL and TSB exhibited the highest antioxidant capacities and therefore could be the main sources of natural antioxidant. An important relationship between total phenolic content was observed showing that the major contributor to the antioxidant properties were phenolic compounds.